Corpo, escola, cognição: experiências em oficinas de dança com alunos do ensino fundamental - Justino, Walderlane Cardoso (2018)
This research aims to investigate the body and its perceptions in the teaching-learning process within the school. The interest in this discussion is due to the perception of a school practice that still neglects the body and dance in their learning relationships. From the dance the research aims to analyze the relationships between body, school and cognition, through two dance workshops, held at the Gilberto Freyre Sociologist school in the city of Recife-PE, with elementary school students. The research builds its foundations in phenomenological thinking with the figure of Maurice Merleau-Ponty (2011), who investigated the body, its sensibilities and perceptions, in dialogue with the theorists Humberto Maturana and Francisco Varela (1995). The latter present in their research studies on the body as cognition. Thus, the theoretical connections between the universe of phenomenology and the biology of knowledge structure the main theoretical corpus of this research. In the area of dance I dialogue with Rudolf Laban (1978) and Pina Bausch for understanding in the theoretical and practical propositions of these researchers an identification with regard to thinking and practice in dance. In the theater I also make a bridge to speak of a thinking and expressive body with Grotowski (1987). The two artistic languages dance and theater are related to the artistic / professional life of the researcher and therefore there is a dialogue between these two universes in the construction of the methodology proposed for the dance workshops held in the course of the research. Focus is a body that dances, reflects, thinks and dialogues. In this perspective, a methodological thought was called what I called Corpo-Olha-Sente-Pensa (COSP) and that during the research was designed along with the practices and theoretical identifications. Isabel Marques (2012) is an important piece in this study also for situating the place of dance in the learning space and also for having a careful and connected look with a body that is social, contextualized and critical. In this way, the research was tracing the ways of bringing a significant bodily experience to the school and to the students, where the daily process of first perception of itself and consequently of the other, was leading the students to discover new relationships of world and learning.